Possible Improvement of Acoustical Climate. Part II: Possible Solutions - WALERIAN, Elżbieta; JANCZUR, Ryszard; CZECHOWICZ, Mieczysław; SMYRNOVA, Yulija (Archives of Acoustics, 2010)
In the paper, the simulation PROP5 program with the road model defined as a noise source and road surroundings model, is used to predict the efficiency of noise protecting means for the chosen building. The appropriate models of verified accuracy have been chosen by comparison of the simulation results with field measurements (Walerian et al., 2010). Here, using the pre-tested simulation program, the possibility of acoustic climate improvement has been analyzed in the ranges of practical variations of the input parameters. The road parameters: its geometry (number of lanes and their positions) and traffic structure over lanes (vehicle flow rates and their average speeds) have been taken under consideration as changeable parameters, that could be corrected to obtain acoustical climate improvement. Moreover, an acoustical screen designing has been considered. The screen efficiency has been evaluated under conditions defined by the input parameters of the road and its surroundings.